Kepuasan Konsumen Terhadap Bauran Pemasaran Rumah Makan “Juli Kuliner” Di Boulevard Kota Manado - Lukar, Melvinia Maria; Kapantow, Gene Henfried Meyer; Tangkere, Ellen Grace (Sam Ratulangi University, 2024)
This study aims to determine the level of customer satisfaction with the marketing mix of Juli Culinary Restaurant in Manado City Boulevard. The data collected in this study are primary data taken by survey with the technique of asking questions directly to consumers, using a questionnaire, and secondary data obtained from the business related to this research, such as the history of the “juli kuliner” restaurant. Sampling by accidental sampling and obtained as many as 88 respondents. The data analysis used in this study is descriptive analysis which is analyzed using an attitude measurement scale or Likert scale. The results showed that in general the level of consumer satisfaction was in the very satisfied category of 84%, with the highest level of satisfaction being the strategic location of 90%. However, there is one variable, namely promotion, which is still in the satisfied category with a satisfaction index of 79%.